Consciousness, Revelation, and Confusion - Luke Roelofs (Dialectica, 2020)
Critics have charged constitutive panpsychism with inconsistency. Panpsychists reject physicalism for its seeming inability to explain consciousness. In making this argument, they commit themselves to the idea of "revelation": that we know, in some especially direct way, the nature of consciousness. Yet they then attribute properties to our consciousness---like being constituted out of trillions of simpler experiential parts---that conflict with how it seems introspectively. This seems to pose a dilemma: either revelation is false, and physicalism remains intact, or revelation is true, and constitutive panpsychists are hoist by their own petard. But this is too simplistic. Constitutive panpsychists can say that our minds contain innumerable phenomenal states that are "confused" with one another: immediately present to introspection only en masse, not individually. Accepting revelation does not require ignoring the attentional, conceptual, and interpretive limitations of introspection, and these familiar limitations remove the tension between panpsychism and relevation.